2013
DOI: 10.3934/molsci.2013.1.27
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Primary cilia in Polycystic Kidney Disease

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is an inherited genetic disorder that results in progressive renal cyst formation with ultimate loss of renal function and other systemic disorders. These systemic disorders include abnormalities in cardiovascular, portal, pancreatic and gastrointestinal systems. ADPKD is considered to be among the ciliopathy diseases due to the association with abnormal primary cilia function. In order to understand the full course of primary cilia and its association with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 108 publications
(137 reference statements)
0
32
0
1
Order By: Relevance
“…First observed by Kowalevsky in 1867 primary cilia were mostly ignored for the next 100 years . However, over the last 20–30 years a growing interest in their behavior has led to the discovery of their role in autosomal dominant polycystic kidney disease (ADPKD) and an increasing range of so called ciliopathies …”
mentioning
confidence: 99%
“…First observed by Kowalevsky in 1867 primary cilia were mostly ignored for the next 100 years . However, over the last 20–30 years a growing interest in their behavior has led to the discovery of their role in autosomal dominant polycystic kidney disease (ADPKD) and an increasing range of so called ciliopathies …”
mentioning
confidence: 99%
“…56 The primary cilia of the collecting duct epithelium function as transmitters of mechano-and chemosensory stimuli to signaling pathways that regulate multiple key cellular processes including differentiation, proliferation, apoptosis, tissue homeostasis and cell polarity. 57 We have previously demonstrated that cystin, with two functional nuclear localization signals, can be released from the ciliary membrane through a myristoyl-electrostatic switch and translocate to the nucleus where it forms a regulatory complex with necdin to modulate Myc expression. 24 The Myc proto-oncogene plays a critical role in normal kidney development 58 and several lines of evidence suggest a central role for dysregulated Myc expression in the pathophysiology of polycystic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…They also act as flow and chemosensors, for example, in the collecting ducts of renal epithelia, where they project into the lumen of the duct and sense bulk filtrate physicochemical properties and flow 28,29 . When these primary cilia are defective, cell growth and proliferation become unregulated, resulting in one of the many possible ciliopathies 4,5 known as polycystic kidney disease 30,31 .…”
Section: Introductionmentioning
confidence: 99%